A Pharmacoeconomic Comparison of Cost Variation among Hypolipidemic Drugs Available in Indian Market - Meghna Shinde; Anjali Kushwah (Universitas Padjadjaran, 2021)
Hyperlipidemia is a major cause of atherosclerotic coronary and cerebrovascular disorders affecting a large Indian population. The cost of various hypolipidemic drugs that are used for the prevention and treatment of these afflictions largely varies in the Indian pharmaceutical market. Our study aimed to evaluate the cost variation of different brands of hypolipidemic drugs and to compare the branded prices with their corresponding generic and ceiling prices. The costs of various drugs were procured from the latest issue of the "Drug Today" from October to November 2020 edition which is a directory of all the drugs available in India published quarterly every year by Lorina Publications (India) Inc. Cost ratio, percent cost variation, and daily defined dose (DDD) were calculated. We also compared the branded prices of drugs with their generic and ceiling prices available on the official website. A total of 9 single hypolipidemic drugs and 9 fixed-dose combinations (FDC) showed a wide per cent cost variation. The highest percentage of cost variation was atorvastatin 80 mg (3284%) whereas fenofibrate showed the lowest percent cost variation (0.91%). The cost ratio was also found higher in 2 from 6 drugs. Among FDCs, atorvastatin 10mg + ezetimibe 10 mg (484%) showed a higher cost variation and rosuvastatin 20 mg + fenofibrate 160mg (0.6%) showed a minimum variation. The maximum cost variation from branded prices compared to generic prices was found in simvastatin 20 mg (544%) and atorvastatin 10 mg (155%). In summary, our study showed a wide variation in the cost of hypolipidemic drugs available in the Indian market which provides an insight to the prescriber, gives drug price control authorities to minimize the financial burden on the patient, and improves their compliance